Sustainability of Self-Efficacy among Nascent Disable Entrepreneurs: A Case Study on Disable’s Home - Firoz, Farhana; Alam, Muntasir (Asian Business Review, 2015)
The study has focused on practicality of self-efficacy theory, and how it helps to build confidence among the disables in building their career choice as entrepreneurs. For this we chose a case study approach on Disable’s home, which is a non- profit organization to provide support for disables. The study was conducted in two phases. First phase, from disable people’s perspective who were trainees in the Disable’s home. And second, from the Disable’s home’s perspective. Findings of the first phase suggest, in order to sustain self-efficacy with regard to career choice as entrepreneurs, not only institutional support is enough but other additional supports like social, financial, family supports  are important. In the second phase, it was observed that institution needs to be resourceful in order to provide proper support to the disables and embed self-efficacy among them. JEL Classification Code:  M31
Keywords: self-efficacy; disable people; Entrepreneurs